Exploring Rat Preserved Media as Teaching Material for Vector Control Subjects - wahyu widyantoro; Samidi samidi (Labor Dasar dan Sentral Universitas Andalas, 2020)
Learning media is one of important parts of the educational process. Direct learning with rats has the potential to have a high risk of student health. Through the learning media for rat preservation, students can understand the learning objectives of mouse identification. Rat preservation is one of the learning media in the Department of Environmental Health, Poltekkes Kemenkes Yogyakarta. The media was used for practical of rats identification as a part of vector controlling subjects. This research aims to develop rat preserved media that could be used as a support for practical activities on vector control for the identification process. The rat media was developed in the form of learning material through defining, designing and development stages. Afterwards it was tested by validity test and the attractiveness. The test of attractiveness was done by taxidermy experts, lecturers, and a group of 30 students who had taken vector control courses. The data obtained through questionnaires and focus group discussions (FGD). The results of the data obtained were then analyzed descriptively and analytically. The research results were reviewed from the aspects of quality, durability, the similarity in shape, and similarity in color. Expert judgment results regarding the aspects of quality, durability, the similarity of shape, and similarity of color were categorized as valid by the taxidermy experts, practitioners, and lecturers. According to the students, 99.6% respondents agreed that the media was suitable as a learning media for mouse identification. The use of rats media can be safety for use as learning media for vector control subjectsjob risk, rats media, safety and health, taxidermy experts, vector controlling subjects.